Montagem e confecção do set up ortodôntico - Porto, Betina Grehs; Raveli, Dirceu Barnabé [UNESP]; Porto, Cecília Helena Soares; Pendenza, Diego Cardoso; Martins, Lídia Parsekian [UNESP] (My University, 2010)
Diagnosis and planning stages are critical to the success of orthodontic treatment, in which the orthodontist should have many elements that contribute to the most appropriate decision-making. The orthodontic set-up is an important resource in the planning of corrective orthodontics therapy. It consists of the repositioning of the teeth previously removed from the study dental casts and reassembled on its remaining basis. When properly made, the set-up allows a three-dimensional preview of problems and limitations of the case, assisting in decision-making regarding tooth extractions in cases with problems of space, amount of anchorage loss extent and type of tooth movement, discrepancy of dental arch perimeter, discrepancy of inter-arch tooth volume, among others, indicating the best option for treatment. This paper outlines the most important steps for its confection, an evaluation system and its application in the preparation of orthodontic treatment planning.

O diagnóstico e o planejamento constituem etapas fundamentais para o sucesso do tratamento ortodôntico, nas quais o ortodontista deve ter inúmeros elementos que contribuem na tomada das decisões mais acertadas. O set-up, ou montagem de diagnóstico em modelo, é um importante recurso no planejamento da terapia ortodôntica corretiva. Consiste no reposicionamento dos dentes previamente removidos dos modelos de estudo e remontados sobre a base remanescente dos mesmos. Quando corretamente confeccionado, o set-up permite uma visualização tridimensional prévia dos problemas e limitações do caso, auxiliando na tomada de decisões quanto às exodontias em casos com problemas de espaços, à quantidade de perda de ancoragem, extensão e tipo de movimentação dentária, discrepância de perímetro do arco, discrepância do volume dentário interarcadas, entre outros, indicando a melhor opção para o tratamento. Este trabalho expõe etapas importantes para sua confecção, sistema de avaliação e sua ap1icação na elaboração de planos de tratamento ortodôntico.
Confection and assembly of orthodontic set-up
Keywords: Plaster casts; Orthodontic diagnosis; Set-up; Modelos de gesso; Diagnóstico ortodôntico; Set-up